The Influence of Biological Literacy and Adolescents' Attitudes Regarding Reproductive Health on Healthy Reproductive Behavior in the 2024 PIK-KRR Program - Nur Sitiyaroh; Iim Rohimah; Lia Lisaadah Hidayati; Siti Marwiyah; Sulistiyarini; Elis Mustika (Postgraduate, University of Mataram, 2024)
Adolescent reproductive health includes physical, mental and social aspects. Apart from being related to physical conditions such as diseases or disorders of the reproductive organs, reproductive health also involves psychological and social well-being which has an impact on the quality of life of teenagers. Factors that influence adolescent reproductive health include individual knowledge and attitudes as internal factors, as well as the family environment, the role of teachers, peers, and access to information as external factors. This research aims to analyze the influence of biological literacy and attitudes of adolescents regarding reproductive health in the PIK-KRR (Adolescent Reproductive Health Information and Counseling Center) program on healthy reproductive behavior in adolescents. This research uses an analytical observational design with a case-control method. The sample was taken proportionally with a 1:1 ratio, consisting of 250 teenagers with non-risky reproductive behavior and 250 teenagers with risky reproductive behavior. Data analysis was carried out using the Chi-square test. The results showed that biological literacy (p=0.000) and attitudes (p=0.000) had a significant effect on healthy reproductive behavior in adolescents. These findings emphasize the importance of knowledge and attitudes obtained from the PIK-KRR program in shaping healthy reproductive behavior.